DETECTION OF AUTO-ANTIBODIES SPECIFIC TO ISLETS CELLS INPATIENTSWITH THYROID DYSFUNCTION BY USING BIOCHIPSTECHNIQUE - Muhammad, Haider J (Al-Nahrain Journal of Science, 2018)
The aim of this study was to detect the auto immune Type 1 diabetes among the disorders with thyroid dysfunction (hyperthyroidism and hypothyroidism).The study included 50 patients suffering from thyroid dysfunction, their aged was from (1-30) years. They were selected randomly from the Al-kindy center for infertility and indocrinology. The control group consisted of (20) healthy subjects comparable for age and sex of study groups. Thyroid function tests (thyroid-stimulating hormone [TSH], thyroxin, and triiodothyronine) measured in by using miniVIDAS system and auto-antibodies for Beta cells in pancreas estimated in the same patients by using immunofluorescent method (IFAT), the method named BIOCHIPS Mosaic. Results of thyroid function test revealed that 25 patients were evaluated to have hyperthyroidism and 25 patients with hypothyroidism and the results of BIOCHIPS showed hyperthyroidism group was having autoantibodies ercent of all the subjects (two from 25 patients) .While there was no signs of auto antibodies for islets cells in hypothyroidism group. The study revealed that the prevalence of thyroid dysfunction was higher in women than men.